2015
DOI: 10.1016/j.jcat.2015.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Fischer–Tropsch synthesis: Effect of ammonia in syngas on the Fischer–Tropsch synthesis performance of a precipitated iron catalyst

Abstract: The effect of ammonia in syngas on the Fischer-Tropsch Synthesis (FTS) reaction over 100 Fe/5.1 Si/2.0 Cu/3.0 K catalyst was studied at 220-270 o C and 1.3 MPa using a 1-L slurry phase reactor. The ammonia added in syngas originated from adding ammonia gas, ammonium hydroxide solution or ammonium nitrate (AN) solution. A wide range of ammonia concentrations (i.e., 0.1-400 ppm) was examined for several hundred hours. The Fe catalysts withdrawn at different times (i.e., after activation by carburization in CO, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 39 publications
(59 reference statements)
4
20
0
Order By: Relevance
“…The results of Mössbauer spectroscopy reflect three important aspects about the behavior of sulfur: 1) χ-Fe 5 C 2 phases were unstable at low temperature conditions, and a fraction of them converted to έ-Fe 2.2 C; 2) the formation of bulk Fe-S compounds as a deactivation mechanism in the current context was ruled out, consistent with the results of XRD; 3) co-feeding sulfur for several hundreds of hours did not alter the distribution of the iron phase, indicating that sulfur adsorbed on iron sites in a uniform manner. έ-Fe 2.2 C and χ-Fe 5 C 2 exhibited better stability at low and high temperatures, respectively, which is consistent with our earlier study [9] and that of a study in the open literature [31]. The lower amounts of iron magnetite found in the used sample at 260 o C relative to the one at 270 o C could be ascribed to a lower extent of oxidation of χ-Fe 5 C 2 by water (3Fe 5 C 2 + 32H 2 O = 5Fe 3 O 4 + 6CO 2 + 32H 2 ).…”
Section: Mössbauer Spectroscopy Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…The results of Mössbauer spectroscopy reflect three important aspects about the behavior of sulfur: 1) χ-Fe 5 C 2 phases were unstable at low temperature conditions, and a fraction of them converted to έ-Fe 2.2 C; 2) the formation of bulk Fe-S compounds as a deactivation mechanism in the current context was ruled out, consistent with the results of XRD; 3) co-feeding sulfur for several hundreds of hours did not alter the distribution of the iron phase, indicating that sulfur adsorbed on iron sites in a uniform manner. έ-Fe 2.2 C and χ-Fe 5 C 2 exhibited better stability at low and high temperatures, respectively, which is consistent with our earlier study [9] and that of a study in the open literature [31]. The lower amounts of iron magnetite found in the used sample at 260 o C relative to the one at 270 o C could be ascribed to a lower extent of oxidation of χ-Fe 5 C 2 by water (3Fe 5 C 2 + 32H 2 O = 5Fe 3 O 4 + 6CO 2 + 32H 2 ).…”
Section: Mössbauer Spectroscopy Resultssupporting
confidence: 93%
“…To understand the deactivation mechanism by sulfur in this study, XRD results of the used catalysts that were exposed to 1.0 ppm H 2 S at 270 o C and 260 o C, as well as clean conditions (i.e., no H 2 S) are provided in Figure 8. Fe 3 O 4 and Fe 5 C 2 phases were detected at 2θ of 30 o , 35.5 o and 40 o , 42.6 o , 45.0 o and 50.5 o respectively, which were also observed on the Fe catalysts exposed to ammonia [9]. Iron-sulfur compounds with sufficient long range order were not detected by XRD, and the distributions of iron carbides and magnetite did not change significantly after sulfur poisoning.…”
Section: Xrd Results Of Used Fe Catalystsmentioning
confidence: 88%
See 2 more Smart Citations
“…In the same study they found no effect of ammonia on the activity of iron catalysts. This is supported by Ma et al 80 , who did not find any negative effect of ammonia on the catalytic activity or selectivity for iron catalysts.…”
Section: Ammonia and Hcnsupporting
confidence: 59%